3, 3′, 5, 5′-Tetramethoxybiphenyl-4, 4′-diol: A new antioxidant enhancing oxidative stability of soybean biodiesel. (1st February 2019) - Schirmann, Jéseka G.; Angilelli, Karina G.; Dekker, Robert F.H.; Borsato, Dionísio; Barbosa-Dekker, Aneli M.
Graphical abstract: Highlights: 3, 3′, 5, 5′-Tetramethoxybiphenyl-4, 4′-diol (TMBP) was obtained through enzyme-catalysis. TMBP as an additive is more sustainable for conserving soybean biodiesel. Induction periods were higher than 6 h at 110 °C established by legislation. Kinetic and thermodynamic parameters of oxidation show the efficacy of TMBP. Antioxidant action of TMBP in biodiesel was compared to tert -butyl hydroxytoluene. Abstract: 3, 3′, 5, 5′-Tetramethoxybiphenyl-4, 4′-diol (TMBP) is described in the literature as having antioxidant activity, and can be obtained through enzyme-catalyzed processes. Its use as an additive to biodiesel offers a more sustainable substitute for the antioxidants commonly used for the conservation of this type of biofuel. In this work, TMBP was synthesized from 2, 6-dimethoxyphenol catalyzed by the laccase from Botryosphaeria rhodina MAMB-05, and applied to soybean biodiesel to evaluate its antioxidant action by the determination of the induction period, and kinetic and thermodynamic oxidation parameters. Biodiesel samples containing TMBP presented induction periods higher than the 6 h in the Rancimat test conducted at 110 °C. The reaction rate constants at all temperatures examined were lower than those obtained for samples containing tert -butylhydroxytoluene (BHT), a common synthetic antioxidant added to biodiesel. The kinetic and thermodynamic parameters of oxidation indicated the effectiveness of TMBP in the inhibition of oxidative processes in soybean biodiesel compared to BHT. The antioxidant action of TMBP was not impaired as a function of thermal degradation, as thermogravimetry analyzes indicated degradation events occurring only above 270 °C.